A manual of Public enlightenment committee on the Second-Tier Foreign Exchange Market - Central Bank of Nigeria (Lagos, Nigeria : Central Bank of Nigeria, 1987)
This manual is the publication of the Central Bank of Nigeria's Public Enlightenment Committee on the Second-Tier Foreign Exchange Market
ijb 12/02/2019
Ref
Keywords: Foreign Exchange; Market regulation; Nigeria